Use of valvometry as an alert tool to signal the presence of toxic algae Alexandrium catenella by Mytilus edulis - Durier, Guillaume; Nadalini, Jean-Bruno; Comeau, Luc A.; Starr, Michel; Michaud, Sonia; Tran, Damien; St-Louis, Richard; Babarro, José M. F.; Clements, Jeff C.; Tremblay, Réjean (Frontiers in Marine Science, 2022)
Valvometry is a non-invasive technique used to continuously monitor gaping behaviour of bivalves at high frequency. In previous laboratory studies, valvometry has revealed a behavioural sensitivity of bivalves to the presence of toxic microalgae in seawater. However, the application of valvometry as an early-warning system for detecting natural occurrences of toxic microalgae and their resulting toxicity in bivalves remains largely unexplored. In this study, valvometry was used to characterise changes in blue mussels (Mytilus edulis) gaping behaviour during gradual exposure to the toxic dinoflagellate, Alexandrium catenella, which produces paralytic shellfish toxins (PST). Laboratory experiments were first performed to identify specific gaping behaviour changes and these responses were subsequently validated in natural seawater conditions in a second experiment. Under both laboratory and natural seawater conditions, mussels exposed to A. catenella tended to remain open (yawning) longer than non-exposed mussels. This change in gaping behaviour was observed at PST concentration as low as 30 μg STXeq 100 g–1 of mussel tissue. We suggest that increased opening is likely related to temporary muscular paralysis induced by toxic algae, as this mechanism has been previously reported in other bivalve species. Furthermore, we observed that biological rhythms of valve behaviour related to tidal and daily rhythms were modified when mussels were intoxicated by PSP (Paralytic Shellfish Poisoning). In conclusion, the effects of toxic algae on mussel gaping behaviour reveals that valvometry could be used as an early-warning tool for the presence of toxic Alexandrium sp. in the environment prior to mussels reaching the regulatory threshold (80 μg STXeq 100 g–1) for harvest interdiction.